ORIGINS, ESTABLISHMENT AND TRADITION OF THE RESEARCH WORK IN LESGAFT NATIONAL STATE UNIVERSITY OF PHYSICAL EDUCATION, SPORT AND HEALTH - Sergey M. Ashkinazi (Высшее образование в России)
The article highlights the stages of formation, traditions and achievements of the research and pedagogical schools at Lesgaft University. The principle of teaching and research unity laid by the University founder Petr Lesgaft remains the base for modern scientific research and pedagogical activity at the University. The paper dwells on the perspectives of research within the cluster «Translational Medicine ».